Research on the Scientific Evolution of the Flavonoid Agathisflavone - Vanessa Cristina Meira de Amorim; Markley Silva Oliveira Júnior; Eduardo Muniz Santana Bastos; Victor Diogenes Amaral da Silva; Silvia Lima Costa (Frontiers Media S.A., 2018)
Purpose: Flavonoids are a group of secondary metabolites of the polyphenols class present in several plant species. Among them, the biflavonoid agathisflavone is of interest since it bears several biological effects that include: antiviral, antitumoral, antiprotozoal and neurogenic actions. In this sense, this study aims to use the important tool of scientific prospecting to assess the level of research development concerning the flavonoid agathisflavone. Methods: The experimental design was carried out through strategic reach with keywords on the PubMed (National Center for Biotechnology Information - NCBI) and Science Direct platforms. The articles were compiled and exported to Microsoft Office Excel 2007, where they were analyzed, stored and distributed in charts organized as to different countries, year of publication of scientific articles and journals RESULTS: The prospective research resulted in the identification of 81 scientific productions, published in several journals, submitted by different countries, in several areas of medical domain and in different years of publication over the last 50 years (1965 - 2018). It was also possible to investigate the advances in the study of agathisflavone for the development of new therapeutics. Conclusion: Although agathisflavone has been known in the literature since at least 1969, only 23 of the eligible articles found evaluated its possible therapeutic effects. The demonstrated biological activities of agathisflavone range from antiprotozoal to neurogenesis and neuroprotection, however, the molecule needs to be better studied at the in vivo and human level.